Supra-coronary Aortic Banding Improves Right Ventricular Function in Experimental Pulmonary Arterial Hypertension in Rats by Increasing Systolic Right Coronary Artery Perfusion - Tian, Lian (Acta Physiol (Oxf), 2020)
AIM: Pulmonary arterial hypertension (PAH) results in right ventricular (RV) dysfunction due, in part, to RV ischemia. The relative contribution of RV microvascular rarefaction versus reduced right coronary artery perfusion pressure (RCA-PP) to RV ischemia is unknown. We hypothesize that increasing RCA-PP improves RV function in PAH by increasing RV systolic perfusion. METHODS: Supra-coronary aortic banding (SAB) or sham surgery was performed on male Sprague-Dawley rats. 7–10 days later, rats received either monocrotaline (MCT; 60mg/kg) or saline. After one month, echocardiography, cardiac catheterization, (99m)Tc-sestamibi single-photon emission computed tomography (SPECT) and microsphere infusion studies were performed. The RV was harvested for measurement of hypertrophy (RVH), fibrosis and immunoblotting, and the lung was harvested for pulmonary artery (PA) histology. RESULTS: SAB increased systolic pressures in proximal aorta and systolic RCA-PP in SAB+MCT vs. MCT rats (114±12 vs. 5±9mmHg), without altering diastolic RCA-PP. SAB+MCT rats had improved RV function versus MCT rats, evident from their significantly increased cardiac output (CO), RV free wall (RVFW) thickening, tricuspid annular plane systolic excursion (TAPSE), and RV-PA coupling indices. RV-PA coupling indices and CO correlated directly with systolic RCA-PP. RV perfusion was increased in SAB+MCT vs. MCT rats and correlated well with CO; whereas microvascular rarefaction was unaltered. SAB+MCT rats had less RVH and fibrosis and lower PA pressures versus MCT rats. SAB+MCT rats had significantly lower RV pyruvate kinase muscle isoform 2/1 ratios than MCT rats, consistent with restoration of oxidative metabolism. CONCLUSION: A SAB-induced increase in systolic RCA-PP improves RV perfusion and function in MCT rats. Maintaining systolic RCA perfusion can preserve RV function in PAH.